DYNAMIC LOT SIZING MODEL FOR RETAILERS WITH MULTI SUPPLIER, QUANTITY DISCOUNTS AND CAPACITY CONSTRAINS - Ferdian, Rendiyatna; Hakim Halim, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Onderhoud is a Small Medium Enterprises (SMEs) engaged in the field of custom shoes production services. Nowadays the company spends a large amount of money on ordering a leather raw material from suppliers. Orders are made to several suppliers every time there is an order. The swelling of production costs was identified due to the amount of the cost of the order made by the company. To reduce production costs, companies need to plan production by determining the optimal order lot to minimize overall production costs. Another limitation that is owned by the company is the production capacity, where in one period (one week) the company is only able to produce 15 units of shoes. In this research, the development of models from pre-existing models is carried out to determine the optimal lot order that must be done by the company. The test results show that the developed model is able to solve the problems faced by the company. Based on the results of testing the data, it can be seen that by using a plan that is carried out using the results of the development model, the company can increase profits by 1.47% compared to using the current ordering method.